PREDICTORS EMPLOYEE PERFORMANCE IN INDONESIAN MANUFACTURING COMPANY USING PATH ANLYSIS - Ekasari, Agustina; Peranginangin, Jasanta (LPPM Universitas Terbuka, 2019)
This research aims to find path analysis that influencing emloyee performance in Indonesia manufacturing company. Design of this research is quantitative methode, There is 150 questionaires spreaded to manufacturing company. This research using multivariate anlysis with Statistical Package for the Social Sciences (SPSS). The result of this paper will described the important factors to build employee performance in manufacturing company. This study will strengtened the previous research about employee performance in manufacturing company. This research finding provides conceptual framework job satisfaction and employee performance. there are six hypotheses developed in this study, there are Four accepted hypotheses and two rejected hypotheses. This research will contributed to the body of knowledge, particularly in human resource management science.